Can Criminal Law Drive Social Change? The Promotional Function and the Affirmative Consent Debate - Fernandez Mejias, Jorge (ETHICS IN PROGRESS, 2026)
The relationship between criminal law and social change has conventionally been conceived as unidirectional: penal statutes reflect, rather than shape, the normative hierarchy of a given society. This article examines the conditions under which the promotional function of criminal law – its deployment, in Bobbio’s sense, as an instrument for installing new social norms rather than merely conserving existing ones – can be considered legitimate. The affirmative consent model in sexual criminal law, as enacted in Spain, serves as the test case against which three analytical perspectives map the boundaries of permissible penal promotion. First, the declaratory perspective holds that, with respect to negative sexual autonomy, the affirmative consent model performs a conservative function, declaring a pre-existing public wrong by reference to shared civic values, while assuming a constitutive function with respect to positive autonomy, thereby exceeding the declaratory warrant of criminal law. Second, the conditioned promotional perspective identifies four cumulative legitimacy criteria and finds the affirmative consent model only partially compliant with them. Third, the normative framing perspective contends that the political rationality structuring affirmative consent reform is oriented toward the legal entrenchment of an interpretative grammar rather than behavioral transformation. The three perspectives converge in finding that the promotional justification of affirmative consent fails to meet the legitimacy requirements applicable to each. The shared conclusion is that whereas criminal law may legitimately perform a conservative function in protecting negative sexual autonomy, it may not legitimately be deployed to entrench a specific communicative model for exercising positive sexual autonomy. The subsidiarity principle is advanced as the criterion that confines criminal law to a consolidating role in cultural transformation, allocating its promotional ambitions to the domain of social and educational policy.